Children’s mental time travel during mind wandering - Ye, Qun; Song, Xiaolan; Zhang, Yi; Wang, Qinqin (Frontiers in Psychology, 2014)
The prospective bias is a salient feature of mind wandering in healthy adults, yet little is known about the temporal focus of children’s mind wandering. In the present study, (I) we developed the Temporal Focus of Mind Wandering Questionnaire for school-age children (TFMWQ-C), a 12-item scale with good test-retest reliability and construct validity. (II) The criterion validity was tested by thought sampling in both Choice Reaction Time Task (CRT) and Working Memory Task (WMT). A positive correlation was found between the temporal focus measured by the questionnaire and the one adopted during task-unrelated thoughts (TUTs) by thought sampling probes, especially in the trait level of future-oriented mind wandering. At the same time, children who experienced more TUTs tended to show worse behavioral performance during tasks. (III) The children in both tasks experienced more future-oriented TUTs than past-oriented ones, which was congruent with the results observed in adults; however, in contrast with previous research on adults, the prospective bias was not influenced by task demands. Together these results indicate that the prospective bias of mind wandering has emerged since the school age (9~13 years old), and that the relationship between mental time travel during mind wandering and the use of cognitive resources differs between children and adults. Our study provides new insights into how this interesting feature of mind wandering may adaptively contribute to the development of children’s mental time travel.